EXPLORING PEER FEEDBACK PRACTICE TO PROMOTE STUDENT EXPERIENCES IN LEARNING WRITING RECOUNT TEXT - Nurjanah, Kartika Dewi; Ambarwati, Evi Karlina; Rahmawati, Maya (IKIP Siliwangi, 2024)
Several high schools in Indonesia show that language is one of the aspects that must be learned for EFL students, especially writing. Providing feedback is an essential role in developing students' writing skills. The students need appropriate feedback methods such as an assessment of writing texts to encourage their writing skills through peer feedback. This research aims to describe the implementation and explore and describe students' experiences providing and receiving peer feedback in writing recount text. This research used a qualitative approach with the case study method through observation and interview. This study was carried out at a senior high school in Karawang. The findings in this study show that students have pretty good experience composing texts. Interaction and peer feedback have helped them better understand the structure and content of recount texts and provide valuable ideas in the writing process. However, although peer feedback is beneficial, teacher feedback must provide correct and detailed direction.